The hunted - Skurzynski, Gloria; Ferguson, Alane (Washington, D.C. : National Geographic Society, 2000)
The Landon family travels to Glacier National Park to investigate why grizzly bear cubs are disappearing and become involved with a ten-year-old Mexican runaway boy.
OSLIS\Gale Nat Geo eBooks(2/2/23).
Map on lining papers.
Description based on print version record.
Keywords: Glacier National Park (Agency : U.S.) -- Juvenile fiction; National parks and reserves -- Juvenile fiction; Grizzly bear -- Juvenile fiction; Bears -- Juvenile fiction; Runaway children -- Juvenile fiction; Glacier National Park (Mont.) -- Fiction; National parks and reserves -- Fiction; Grizzly bear -- Fiction; Bears -- Fiction; Runaways -- Fiction; Mystery and detective stories; Electronic books- OSLIS; Mystery fiction; Electronic books